Historische Quellen im DaF-Unterricht - Hieronimus, Marc (Universitätsverlag Göttingen, 2012)
The contributions of this book are the results of a conference of the German Academic Exchange Service (DAAD) in March 2011. The underlying consideration was simple: In language teaching and cultural studies, media are essential - why not resort to historical sources? They can be used in many ways, have a high recognition value and offer innumerable points of contact to the topics of regional and media studies. First, relevant experts present the most important collections and portals on the Internet and enter into the question of the informative and practical value of historical sources. The second part deals in a more detailed manner with aural sources, movies, political cartoons and posters as well as street names and texts of worker literature.